Social work and health care practice with transgender and nonbinary individuals and communities : voices for equity, inclusion, and resilience - Kattari, Shanna K. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines issues across the lifespan of transgender and nonbinary individuals whilst synthesizing conceptual work, empirical evidence, pedagogical content, educational experiences, and the voices of transgender and nonbinary individuals. It highlights the incredible resilience and resistance of transgender and nonbinary individuals and communities to challenge narratives that rely on a one-dimensional perspective of risk and tragic lives. While there is currently unprecedented visibility and increasing levels of support and acceptance, members of these communities still face shockingly high rates of violence, victimization, unemployment, discrimination, and family rejection. The significant need for services and support coupled with social, clinical, and medical service systems ill-equipped to provide culturally responsive care illustrates the critical need for quality education and training of educators, practitioners, and service providers in best practices of working with members of the transgender and nonbinary community"--
OCLC-licensed vendor bibliographic record.
Keywords: Transgender people -- Civil rights; Transgender people -- Social aspects; Gender-nonconforming people; Social work with transgender people; SOCIAL SCIENCE / Social Work